ФОРМУВАННЯ ПЕДАГОГІЧНОЇ КОМПЕТЕНТНОСТІ У МАЙБУТНІХ ПЕДАГОГІЧНИХ ПРАЦІВНИКІВ У ПРОЦЕСІ ВИВЧЕННЯ КУРСУ „ПРОФЕСІЙНА ПЕДАГОГІКА” (Педагогіка вищої та середньої школи, 2008)
The problem of determination of ways of forming pedagogical competence for future masters of production study and teachers of the special objects is examined in the article. Approaches of scientists to determination of competence are analyzed. It is underlined, that direction on a model, which includes pedagogical abilities from the point of view of basic operating functions of the pedagogies, is providing forming of pedagogical competence.